1998
DOI: 10.1111/j.1528-1157.1998.tb01387.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phenytoin, Carbamazepine, and Gabapentin on Calcium Channels in Hippocampal Granule Cells from Patients with Temporal Lobe Epilepsy

Abstract: Summary: Purpose:The anticonvulsants phenytoin (PHT), carbamazepine (CBZ), and gabapentin (GBP) are commonly used in the treatment of temporal lobe epilepsy. Ca" current modulation has been proposed to contribute to the antiepileptic activity of these drugs. The purpose of this study was to determine the effects of these anticonvulsants on voltage-dependent calcium channels in pathologically altered neurons from patients with chronic temporal lobe epilepsy.Methods: Acutely isolated human hippocampal granule ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(56 citation statements)
references
References 39 publications
2
54
0
Order By: Relevance
“…These data indicate that CBZ, at least at higher concentrations, can affect L-type Ca 2 + channels, and agree with other findings indicating that CBZ could have Ca 2 + antagonistic properties (Elliott, 1990;Schirrmacher et al, 1993;Mark et al, 1995;Vonwegerer et al, 1997;Schumacher et al, 1998). Moreover, Schirrmacher et al (1995) also suggested that CBZ reduces Ca 2 + currents presumably by inhibiting L-type Ca 2 + channels in rat sensory spinal ganglion cells.…”
Section: Effect Of Cbz On Kainate-mediated [Ca 2 + ] I Responsessupporting
confidence: 80%
See 1 more Smart Citation
“…These data indicate that CBZ, at least at higher concentrations, can affect L-type Ca 2 + channels, and agree with other findings indicating that CBZ could have Ca 2 + antagonistic properties (Elliott, 1990;Schirrmacher et al, 1993;Mark et al, 1995;Vonwegerer et al, 1997;Schumacher et al, 1998). Moreover, Schirrmacher et al (1995) also suggested that CBZ reduces Ca 2 + currents presumably by inhibiting L-type Ca 2 + channels in rat sensory spinal ganglion cells.…”
Section: Effect Of Cbz On Kainate-mediated [Ca 2 + ] I Responsessupporting
confidence: 80%
“…However, the mechanisms underlying the effects of this AED have not been completely identified, and are still a matter of debate. It has been shown that CBZ can inhibit Ca 2 + channels (Elliott, 1990;Schirrmacher et al, 1993;Schumacher et al, 1998), enhance 4-aminopyridine-sensitive potassium currents in cortical neurons (Olpe et al, 1991), acts as an antagonist of adenosine A 1 receptors (Biber et al, 1996), attenuates cAMP production (Chen et al, 1996), induces the release of serotonin (Dailey et al, 1997a,b), and inhibits the release of glutamate (Waldmeier et al, 1996;Okada et al, 1998). Preischemic treatment with CBZ also tends to reduce the cerebral damage and neurological deficit (Minato et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Six neurons remained unidentified. HVA Ca2+ currents were evoked every 10 sec with a 50-msec depolarizing voltage step to -10 mV from a holding potential of -60 mV using Ba2+ (5 mM) as the charge carrier (29). The peak current amplitudes at -10 mV ranged from 360 pA to 2.50 nA (mean 1.48 f 0.49 nA, n = 47), producing a mean current density of 149 f 70 pA/pF.…”
Section: Resultsmentioning
confidence: 99%
“…Dissociated neurons from the dentate gyrus were obtained from human specimens as described previously (29,30). Briefly, surgical specimens were dissected into 400-pm-thick coronal hippocampal slices with the use of a vibratome (Ted Pella Inc., Redding, Calif, U.S.A.).…”
Section: Preparation Of Acutely Isolated Neuronsmentioning
confidence: 99%
“…In the past 30 years, many types of spontaneous or pharmacologically induced animal "absence-like" epilepsy have been reported (HOSFORD et al, 1995;MAXSON et al, 1983;SIDMAN, 1979;SERIKAWA et al, 1987;COENEN, 1986;VERGNES et al, 1982VERGNES et al, , 1986, with cortical spike-and-wave discharge, associated with various behavioral phenomena, as common denominator. A presumably new type of spontaneous epilepsy, resembling human absence seizures, was identified in a fraction of Wistar rats used in our laboratory.…”
Section: Introductionmentioning
confidence: 99%